Positive obligations of states for the protection of prisoners’ rights under the case law of the european court of human rights - Urgan, Güven (My University, 2013)
Günümüz insan hakları hukukundaki yaygın somutlaşma sürecinin önemini takdir etmekle birlikte, bu tez mahkum haklarına özel atıfla insan hakları teorisi ve pratiğinde devletlerin pozitif yükümlülüklerinin sınırlı yapısını ortaya koymayı hedeflemektedir. Devletlerin pozitif yükümlülükleri kavramının genel bir referans noktası olarak kullanılagelmekte olmasına rağmen, tez kavramın mevcut kullanımının insan hakları teorisi ve pratiğinin temel yapısı içinde hala var olmaya devam eden yanlış anlaşılmaların etkisi altında olduğunu öne sürmektedir. Yeterince sorgulanarak anlaşılamadığından dolayı, böylesine yanlış bir varsayım devletlerin kuramsal olarak açık yükümlülüklerinin var olduğu özel bir insan hakları uygulama alanında yapılacak hukuksal yorumların kapsamını ve objektifliğini engellemekte ya da sınırlandırmaktadır. Uluslararası insan hakları koruma mekanizmalarınca taraf devletlere tanınan takdir yetkisinin göreceli sınırlılığına ve insan hakları standartlarının her bir bireye bulunduğu devlette sunulması gereken asgari gereklilikler olduğuna ilişkin yapılan sözde vurguya rağmen, evrensel insan hakları söylemi ve pratiği; Avrupa İnsan Hakları Mahkemesinin analiz edilen içtihadı kapsamında tezin de ifade gösterdiği şekilde, insan hakları teorisinde mevcut dikotomik yanlış anlaşılmadan hala olumsuz olarak etkilenmektedir. Dolayısıyla tez, Avrupa İnsan Hakları Mahkemesi’nin mahkum haklarına ilişkin içtihatlarını değerlendirerek pozitif yükümlülüklerin insan hakları teorisindeki ikincil statüsü hakkında ileri sürdüğü teorik argümanların geçerliliğini analiz etmeye çalışmaktadır.

Acknowledging the importance of widespread concretisation process in contemporary human rights law, this dissertation aims at illustrating the limited nature of positive obligations of Acknowledging the importance of widespread concretisation process in contemporary human rights law, this dissertation aims at illustrating the limited nature of positive obligations of States in human rights theory and practice with a special reference to prisoners’ rights. Despite the fact that the concept of positive obligations of States has been widely used as a point of reference, the dissertation posits that its practice has still under the impact of misunderstandings which still do exist within the very fabric of human rights theory and practice. Since it has not been appropriately examined and understood, such a misleading assumption can hinder or delimit the scope and objectiveness of legal interpretation in a specific realm of human rights practice within which States do have explicit hypothetical obligations. Despite the ostensible emphasis that the margin of appreciation introduced to State Parties by the international human rights protection mechanisms is relatively limited and that human rights standards are the minimum requirements that should be provided for each and every individual in a given State, universal human rights discourse and practice are still being negatively affected from, as the dissertation proclaims under the light of the analysed case law of the European Court of Human Rights, the dichotomised (mis)understanding in human rights theory. Accordingly, the dissertation reviews the case law of the ECtHR expounded upon prisoners’ rights so as to analyse the validity of its theoretical arguments about the secondary status of positive obligations in human rights theory.
Keywords: Avrup İnsan Hakları Mahkemesi; Avrupa Birliği; İnsan Hakları; Uluslararası İlişkiler